Neurofibromatosis Type 1 with Highly Active Relapsing-Remitting Multiple Sclerosis (RRMS) - Ciotti, Silvia (Eur J Case Rep Intern Med, 2021)
Neurofibromatosis type 1 (NF1) is an autosomal dominant neurocutaneous disease which confers an increased risk of malignant tumour development. Relapsing remitting multiple sclerosis (RRMS) is an inflammatory demyelinating disease of the central nervous system. The coexistence of multiple sclerosis and NF1 is rare but has been reported. Here, we describe the case of a 31-year-old man with NF1 and subacute walking problems with proximal pain in the lower limbs who was successfully treated with natalizumab. LEARNING POINTS: The coexistence of multiple sclerosis (MS) and neurofibromatosis type 1 (NF1) is very rare but has been described in the literature. Follow-up of patients with NF1 is important as the early detection and management of MS can prevent further disability. Appropriate treatment and physical therapy can improve the patient’s activity and social life.